Organic acid metabolism changes during postharvest dehydration process in grape (Vitis vinifera L.) berries. - Soares, Flávio (2016)
After detachment from the plant and until cell death, fruits remain metabolically active, resulting in compositional modifications . For certain food products, postharvest controlled stresses are applied to induce desired physical or chemical changes . In the case of grapes, a gradual dehydration process is normally utilized for raisin production and also for the production of special wines [ 1 ] . Postharvest dehydration, in general, causes changes in texture, color, taste and nutritional value of food due to the high temperatures and long drying times required in the process [ 2 ] . Present in all plants, organic acids support various and different aspects of cellular metabolism and have great influence in the organoleptic properties of wines and grape juices [ 3 , 4 ] . Little is known, however, regarding how the organic acid metabolism is affected by such industrially applied dehydration processes . Thus, to better understand the metabolism of the organic acids during postharvest dehydration, we applied an industry - mimicking slow dehydration process for eleven days at 50 ºC to intact berry clusters and employed several molecular and biochemical techniques .